Monetary policy transparency, public commentary, and market perceptions about monetary policy in Canada - Pierre L. Siklos (Deutsche Bundesbank, 2000)
The introduction of inflation targets in Canada in 1991 ostensibly clarified the objectives of monetary policy, namely the pursuit of price stability. In doing so, one of the objectives of the new policy was to ensure that the public would henceforth be able to assess more easily monetary policy performance based on the Bank of Canada's record at achieving low and stable inflation. An obvious question then is to ascertain whether in fact, as the Governor the Bank stated recently, "... public commentary on monetary policy since 1991 has involved a fairer assessment of the performance of the Bank of Canada." Using information compiled on commentary about the Bank of Canada, and monetary policy in general, collected from the Globe and Mail and Financial Post national newspapers, we evaluate how favourable or critical such commentaries have been since 1986. In so doing, we examine a sample before inflation control targets were introduced, as well as the period since. The Bank of Canada also aims to influence expectations and financial market perceptions of its performance. Additional tests, using daily interest rate and exchange rates and monthly inflation and inflation forecast data, are presented which shed light on this question. – – Die Einführung von Inflationszielen in Kanada im Jahr 1991 verdeutlichte angeblich das Ziel der Geldpolitik, nämlich Preisstabilität. Mit der neuen Politik sollte unter anderem die Öffentlichkeit fortan den Erfolg der Geldpolitik leichter daran messen können, inwieweit es der Bank von Kanada gelingt, die Inflation stabil auf niedrigem Niveau zu halten. Deshalb liegt die Frage nahe, ob tatsächlich - wie der Präsident der Zentralbank kürzlich feststellte - ' ... die Erfolge der Bank von Kanada in der öffentlichen Kommentierung der Geldpolitik seit 1991 fairer beurteilt werden.' Anhand von Kommentaren in den überregionalen Zeitungen Globe and Mail und Financial Post, die sich mit der Bank von Kanada sowie der Geldpolitik allgemein befassen, werten wir aus, wie positiv oder kritisch diese Kommentare seit 1986 ausgefallen sind. Dabei untersuchen wir eine Stichprobe aus der Zeit vor Einführung der Inflationsziele sowie aus der Zeit danach. Die Bank von Kanada versucht auch, die Erwartungen und die Einschätzung ihrer Politik an den Finanzmärkten zu beeinflussen. Ob ihr dies gelingt, wird mit Hilfe von zusätzlichen Tests untersucht, die sich auf tägliche Zinssätze und Wechselkurse sowie monatliche Inflationsdaten und Inflationsprognosedaten stützen.
Keywords: 330; Geldpolitik; Inflation Targeting; Staatliche Information; Öffentliche Meinung; Finanzmarkt; Inflationserwartung; Schätzung; Kanada